EBSTEIN’S ANOMALY AND ITS MORPHOLOGICAL FORMS, ANTENATAL HISTORY AND GENETIC FACTORS IN THE EVENT OF ANOMALOUS SITUATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Ebstein’s anomaly is a rare malformation of the tricuspid valve, accounting for